Exploring Iranian EFL teachers’ attitudes toward the use of learning management systems in English classes - Fathi, Jalil; Mohammaddokht, Farnoosh; Afzali, Maryam (Íkala, Revista de Lenguaje y Cultura, 2023)
This research was set to uncover Iranian English-as-a-foreign-language (EFL) teachers’ attitudes toward the use of learning management systems (LMS) in English classes. Employing a mixed methods research design, the researchers recruited 168 Iranian EFL teachers from several schools and language institutions as research participants and sent them a valid self-report questionnaire to gather quantitative data. Simultaneously, they conducted semi-structured interviews with 15 teachers to collect qualitative data. Findings revealed that Iranian EFL teachers adopted both positive and negative perceptions of LMS use. The positive perceptions included ease of access, knowledge sharing, suitability for crowded classes, variety of learning tasks, and more advanced assignments and feedback. In turn, negative views comprised inadequacy of teacher training programs, inappropriacy for productive skills, complexity of functions, and students’ unfamiliarity with the systems as well as lack of interest. These results may offer significant insights into EFL practitioners’ perceptions of a variety of measures that can be taken by teacher development programs to encourage the use of LMS in EFL contexts.